Impact of Membrane Fusion and Proteolysis on SpoIIQ Dynamics and Interaction with SpoIIIAH - Chiba, Shinobu (2006)
The onset of engulfment-dependent gene expression during Bacillus subtilis sporulation requires the forespore membrane protein SpoIIQ, which recruits mother cell proteins involved in late gene expression to the outer forespore membrane. Engulfment activates the late forespore transcription factor σ(G), which produces high levels of the secreted SpoIVB protease that is required for activation of the late mother cell transcription factor σ(K). Engulfment also triggers the proteolytic cleavage of SpoIIQ, an event that depends on the SpoIVB protease but not on σ(G) activity. To determine if SpoIVB directly cleaves SpoIIQ and to determine if this event participates in the onset of late gene expression, we purified SpoIVB, SpoIIQ, and SpoIVFA (another SpoIVB substrate). SpoIVB directly cleaved SpoIIQ at the same site in vitro and in vivo and cleaved SpoIVFA in at least three different locations. SpoIIQ cleavage depends on membrane fusion, but not on σ(G) activity, suggesting that the ability of SpoIVB to cleave substrates is regulated by membrane fusion. We isolated SpoIVB-resistant SpoIIQ proteins by random mutagenesis of codons at the cleavage site and demonstrated that SpoIIQ processing is dispensable for spore formation and for activation of late forespore and mother cell gene expression. Fluorescence recovery after photobleaching analysis demonstrated that membrane fusion releases SpoIIQ from an immobile complex, an event that could allow SpoIVB to cleave SpoIIQ. We propose that this membrane fusion-dependent reorganization in the complex, rather than SpoIIQ proteolysis itself, is necessary for the onset of late transcription.